Co-Branding and Brand Repositioning Ramayana Sabar Subur: Consequences of Retail Acquisition in the Midst of a Pandemic - Muhamad Husni Mubarok; saful mujab (Bajang Institute, 2022)
Amid the fluctuating Covid-19 pandemic, PT. Ramayana Lestari Sentosa (RALS) took over the Toserba Sabar Subur from PT. Subur Makmur Sentosa. Previously, experts never predicted that the acquisitions would occur in retail because people's purchasing power was so weak during a pandemic. However, a bold step was taken by RALS which opened several outlets of Ramayana Sabar Subur in Tangerang. This research was conducted to explore the managerial’s point of view in calculating the benefits of the local brand of Sabar Subur and to explore the management strategy of RALS in creating a fresher image of Toserba Sabar Subur without causing ambiguity between Sabar Subur and Ramayana. This research was descriptive with a qualitative approach using a case study method. The researcher used in-depth interviews, questionnaires, and literature in collecting the data. The results show that Co-Branding and Brand Repositioning have been implemented by the management of Ramayana Sabar Subur through four stages: fact finding, planning decisions, communication-action, and evaluation, have a positive impact on the image of the new Sabar Subur. However, the sales profit was not as good as the company's image. This is due to two things: (1) Ramayana Sabar Subur's market share tends to be the lower middle class who are vulnerable during a pandemic; (2) a marketing strategy that is still conventional and does not yet have a qualified digital team.